KARAKTERISTIK MEKANIK KAYU KAMPER SEBAGAI BAHAN KONSTRUKSI - Chauf, Kusnindar A. (MEKTEK, 2005)
Mechanic characteristic is needed for efficiency and optimalization of wood as structural member, so that it can be placed in order of construction. By conducting mechanics test refered to ISO 1975, it could be examined a mechanics characteristics of wood as a base of structural aplication. In this case the flexure strength capacity (MOR) is 89.989 MPa and flexure elasticity (MOE) is 13260 MPa. Parallel tension strength (s//), parallel compression strength (stk//), and shear strength (t//) are 126.913 MPa, 0.4s// and 10,913 MPa respectively. The type of collapse is elastic linier; the brittle collapse will be happened in tension on the otherhand elastics and non linier collapse will be happened in flexure, compression as well as shear. Average mechanic intencity of Kamper will increase if the water content is decrease and the highest increasing on the parallel compression capacity, i.e. 50,5% if it is compared to dried and green condition